Data mining and other Data base techniques for PhD thesis preparation - Karur, Srinatha NA; Ramana Murthy, M.V. (Transactions on Engineering and Computing Sciences, 2015)
The authors in this paper present the role of Data mining and Data base techniques for estimate the quality of thesis or dissertation at Research level. The Doctorate Research consists of various components which are highly defined by University Research Committee or any other concerned authorities. For all general cases the thesis book consists of different chapters with different aims. Each and every chapter has its own identity and constantly has relation with previous chapters. The authors use different Data mining and Data base techniques for determine the correlation between different entities which are involved in the thesis such as page numbers, references, diagrams, equations , graphs, different concepts covered in the thesis book.